2017
DOI: 10.1126/sciadv.1601659
|View full text |Cite
|
Sign up to set email alerts
|

Toward garnet electrolyte–based Li metal batteries: An ultrathin, highly effective, artificial solid-state electrolyte/metallic Li interface

Abstract: Strategy to change the wettability of the solid-state electrolyte against Li and reduce interface resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
506
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 712 publications
(543 citation statements)
references
References 57 publications
9
506
4
Order By: Relevance
“…[130] In addition to Si and Au, the film coating of ZnO, Ge, and Al have similar advantages. [134,136,137] Surprisingly, the surface coated with ultrathin Al 2 O 3 from atomic layer deposition (ALD) effectively negates the interfacial resistance from 1710 to 1 Ω cm 2 , as illustrated in Figure 17c and provides a stable voltage of 13 mV in Li plating and stripping plots (Figure 17d). [133] Schematic diagrams in Figure 17a also demonstrate that the Al 2 O 3 film wetting the solid electrolyte surface results in a compact interfacial contact, which is consistent with the SEM images in Figure 17b.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[130] In addition to Si and Au, the film coating of ZnO, Ge, and Al have similar advantages. [134,136,137] Surprisingly, the surface coated with ultrathin Al 2 O 3 from atomic layer deposition (ALD) effectively negates the interfacial resistance from 1710 to 1 Ω cm 2 , as illustrated in Figure 17c and provides a stable voltage of 13 mV in Li plating and stripping plots (Figure 17d). [133] Schematic diagrams in Figure 17a also demonstrate that the Al 2 O 3 film wetting the solid electrolyte surface results in a compact interfacial contact, which is consistent with the SEM images in Figure 17b.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…For all-solid-state batteries, solide lectrolytes bring several advantages, [1][2][3][4][5][6] such as enhanced safety,i ncreased energy density,s olid device integration, and packaging;t hese expand the operation temperature range and potentially improve cycling stabilitya nd lifetime. Suc-cessfule xamples in oxidesi nclude garnet oxides, [15,16] perovskite-type oxides, [17,18] and antiperovskite oxides. [7,8] In principle, ideal solid electrolytes are expected to have several features: [9][10][11][12][13][14] 1) fast ion dynamics and negligible electronic conductivity (minimum ionic conductivity of 10 À4 Scm À1 at room temperature for practical consideration);2 )a wide electrochemical potential window for battery cycling;3 )ane xceptional mechanical strength to suppress lithium dendrite growth;4 )excellent thermal stability during the cycling processes;and 5) asimple and low cost synthetic process for large-scale applications.…”
mentioning
confidence: 99%
“…Suc-cessfule xamples in oxidesi nclude garnet oxides, [15,16] perovskite-type oxides, [17,18] and antiperovskite oxides. Suc-cessfule xamples in oxidesi nclude garnet oxides, [15,16] perovskite-type oxides, [17,18] and antiperovskite oxides.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] In comparison to those efforts,a na ll-in-one strategy is to use as olid-state electrolyte to replace polymer separators and physically block the Li dendrite penetration [15][16][17][18][19][20][21][22] Theu se of as olid-state electrolyte has many advantages over organic liquid electrolyte in batteries;f or example,as olid-state electrolyte generally has aw ide stability window (0-5 V), good thermal stability,a nd an intrinsic nonflammability. [26,27,46] These metals react with Li at high temperature to form Li-rich solid solutions,a nd in addition, the reaction process improves the wettability of the garnet electrolyte, thus promoting good physical contact with the Li metal at the interface.Generally,i ti sa ssumed that the interface layer would form and stay between the Li metal and the garnet solid electrolyte.Inthis work, we found that the metal coating (Mg is used in this study) diffused from the interface when attached to amolten piece of Li. [20,[23][24][25][26][27][28][29][30][31][32][33] Amajor challenge of using the garnet solid-state electrolyte in aL im etal battery is the poor contact at the interface between the garnet and the Li metal, leading to ah igh interfacial impedance of 10 2 -10 3 ohm cm À2 .E xtensive work has been reported to reduce the interfacial impedance,f or example,b ym odifying solid electrolyte composition, using gel or polymer interlayers,a nd constructing interface structures.…”
mentioning
confidence: 99%
“…[20,[23][24][25][26][27][28][29][30][31][32][33] Amajor challenge of using the garnet solid-state electrolyte in aL im etal battery is the poor contact at the interface between the garnet and the Li metal, leading to ah igh interfacial impedance of 10 2 -10 3 ohm cm À2 .E xtensive work has been reported to reduce the interfacial impedance,f or example,b ym odifying solid electrolyte composition, using gel or polymer interlayers,a nd constructing interface structures. [26,27,46] These metals react with Li at high temperature to form Li-rich solid solutions,a nd in addition, the reaction process improves the wettability of the garnet electrolyte, thus promoting good physical contact with the Li metal at the interface. [26,27,46] These metals react with Li at high temperature to form Li-rich solid solutions,a nd in addition, the reaction process improves the wettability of the garnet electrolyte, thus promoting good physical contact with the Li metal at the interface.…”
mentioning
confidence: 99%